Organizational Change Management: A study on the need for a re-structured organization within a functional configuration - Al Marzouqi, Abdulla Ibrahim Abdulla (2009)
The objective of this study was to qualitatively examine the current organizational structure and systematically investigate and review proposed changes at an Oil Refining Organization. In this study a critical investigation will be conducted to mainly identify and recommend relevant dimensions of a new organizational structure and offer some tentative recommendations to the optimal approach in a project organizational selection context in order to help the current organization overcome cuncurrent organizational difficulties pertaining to managing projects. First, a look at the three major organizational forms commonly used namely, functional, matrix and projectized organizational forms will be conducted, and how each is currently fitted into the current organization. Each of these forms will be investigated in terms of its pros and cons and expected effect on the parent organization. In addition, advantages and disadvantages of the proposed changes and the overall strategic leadership necessary to successfully implement the assigned projects within the framework of the newly discussed organizational structure will be looked into. Then, critical factors that might lead to choosing one form of structure over the others will be discussed by deciding about how to tie projects to the parent organization and how to organize the project teams. In a latter part of this paper a discussion on how a project management team can be organized and then consider some combination of the fundamental forms and examine the implications of using different forms of organizational structures. Finally, a conclusion will be drawn on factors influencing the choice of the optimum organizational structure and the difficulties pertaining to deciding it should be explained. Moreover, some of the critical success factors that might lead to choosing one from of organization over the others and some details of the project team, and describing the various roles of the project staff will be examined. The details of organizing the project team as part of the new organization structure will be investigated as to describe the roles of the project staff in their constituent sections under the newly proposed organization, which will be looked into in details. It will also be concluded that in a functional organization, the introduction of projectized structure for the newly introduced organization may significantly increase the probability of successful outcome from projects.